A novel nylon membrane-rhodamine 6G spirocyclic phenylthiosemicarbazide derivative system as a fluorimetric probe for mercury(ii) ion - Lozano, Valeria Antonella (2012)
A highly sensitive and selective probe for the fluorimetric determination of mercury ion traces in aqueous solution is proposed. The probe is based on the mercury-promoted ring opening of the spirolactam moiety of a rhodamine 6G spirocyclic phenylthiosemicarbazide derivative (FC1) retained in nylon membranes. It is demonstrated that the chemodosimeter preserves its sensor ability, displaying intense fluorescence in the presence of Hg(II) after being immobilized on the nylon surface and reacting with the mercury ion solution via a simple syringe procedure. The advantages of this proposal are: (1) the use of an easily affordable solid support which is able to immobilize the FC1 molecular probe without involving a covalent bond, (2) the consumption of a very small volume of organic reagent, dramatically reducing the environmental impact, and (3) the development of a solid phase system potentially useful as a main component for designing chemical sensors capable of providing continuous real-time information. In order to obtain higher and stable fluorescence signals, both experimental and instrumental variables were optimized. Thus, a simple and sensitive fluorescence method for the determination of mercury ion was established. The limit of detection calculated according to 1995 IUPAC Recommendations was 0.4 ng mL-1 (lower than the toxic levels in drinking water for human consumption, established by several regulatory agencies), the relative standard deviation was 2.3% (n= 6) at a level of 3.5 ng mL-1, and the sampling rate was about 15 samples per hour. The study of the potential interference from common cations demonstrated a remarkable selectivity for the investigated metal ion. The viability of determining Hg(II) ion residues in real water samples was successfully evaluated through the recovery study of several spiked environmental water samples from different locations.